Community multiculturalism and self-reported immigrant crime: Testing three theoretical mechanisms - Arjen Leerkes; Tineke Fokkema; Jonathan Bening (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2020)
There is considerable contextual variation in crime among immigrants and their native-born descendants, and this study aims to understand that variation better. It examines whether municipal variation in self-reported crimes among Turkish- and Moroccan-Dutch men living in 35 representative Dutch cities (N=911), including the four largest cities, is associated with municipal variation in multicultural attitudes, or 'community multiculturalism', among the native-Dutch (N=2,556). We propose, and test, a mechanism-based theoretical model that links Berry's acculturation theory to general strain theory, social bonding theory, and collective efficacy theory. Evidence is found for a protective effect of community multiculturalism for immigrant crime, which is mostly explained by collective efficacy theory with somewhat weaker evidence for general strain theory and social bonding theory. We discuss implications for the discussion on the (dis)advantages of multiculturalism, and suggest various avenues for further inquiry into immigrants' 'context of reception', and how the acculturation attitudes among established groups affect social cohesion outcomes in multi-ethnic societies.
Keywords: K13; I30; Y80; O15; 330; acculturation theory; immigrant crime; context of reception; local-level variation; migration